The optimized nourishing environment for cultivation of Podisus maculiventris Say. (Heteroptera: Pentatomidae) - Мороз, М. С. (Scientific Progress & Innovations, 2016)
It is set that an optimized nourishing environment for cultivation of Podisus maculiventris Say. provides the high level of development of population. The offered nourishing environment provides a survival at certain high level, a reduction to duration of post-embryonic development, an increase of indexes of mass of imago, amount of the set aside eggs. The predatory bedbugs grown on a nourishing environment are able to find and destroy for a day on 27,91 and 41,86 percents more eggs of the Colorado potato beetle comparatively with a control variant.